NMDA receptors regulate GABA(A) receptor lateral mobility and clustering at inhibitory synapses through serine 327 on the γ2 subunit - Muir, James (National Academy of Sciences, 2010)
Modification of the number of GABA(A) receptors (GABA(A)Rs) clustered at inhibitory synapses can regulate inhibitory synapse strength with important implications for information processing and nervous system plasticity and pathology. Currently, however, the mechanisms that regulate the number of GABA(A)Rs at synapses remain poorly understood. By imaging superecliptic pHluorin tagged GABA(A)R subunits we show that synaptic GABA(A)R clusters are normally stable, but that increased neuronal activity upon glutamate receptor (GluR) activation results in their rapid and reversible dispersal. This dispersal correlates with increases in the mobility of single GABA(A)Rs within the clusters as determined using single-particle tracking of GABA(A)Rs labeled with quantum dots. GluR-dependent dispersal of GABA(A)R clusters requires Ca(2+) influx via NMDA receptors (NMDARs) and activation of the phosphatase calcineurin. Moreover, the dispersal of GABA(A)R clusters and increased mobility of individual GABA(A)Rs are dependent on serine 327 within the intracellular loop of the GABA(A)R γ2 subunit. Thus, NMDAR signaling, via calcineurin and a key GABA(A)R phosphorylation site, controls the stability of synaptic GABA(A)Rs, with important implications for activity-dependent control of synaptic inhibition and neuronal plasticity.